2019
DOI: 10.1002/jcb.28773
|View full text |Cite
|
Sign up to set email alerts
|

The promising novel biomarkers and candidate small molecule drugs in lower‐grade glioma: Evidence from bioinformatics analysis of high‐throughput data

Abstract: Overall survival of patients with low‐grade glioma (LGG) has shown no significant improvement over the past 30 years, with survival averaging approximately 7 years. This study aimed to identify novel promising biomarkers of LGG and reveal its potential molecular mechanisms by integrated bioinformatics analysis. The microarray datasets of GSE68848 and GSE4290 were selected from GEO database for integrated analysis. In total, 293 overlapping differentially expressed genes (DEGs) were detected using the limma pac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…Although Gross et al observed a ubiquitous overexpression of GABRD across various cancer types in the TCGA dataset, these authors did not go any further to explore the prognostic significance of GABRD overexpression in specific tumor types [10]. GABRD has also been referred to in tumors in several other studies [9,11,38,39], but many of these are based on bioinformatic data and the functional relevance of GABRD to carcinogenesis and tumor progression remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Although Gross et al observed a ubiquitous overexpression of GABRD across various cancer types in the TCGA dataset, these authors did not go any further to explore the prognostic significance of GABRD overexpression in specific tumor types [10]. GABRD has also been referred to in tumors in several other studies [9,11,38,39], but many of these are based on bioinformatic data and the functional relevance of GABRD to carcinogenesis and tumor progression remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…GBM is one of the most commonly seen primary malignant brain tumor in adults with an overall poor prognosis (Ostrom et al, 2018;Zhang et al, 2019;Jin et al, 2020). The recurrence rate of GBM is particularly high.…”
Section: Discussionmentioning
confidence: 99%
“…The human interactome map has a higher coverage on proteins encoded by human genes; therefore, it can provide additional insights than those based only on pathway databases. Moreover, PPI networks have been used to infer candidate genes for different types of cancer (44)(45)(46)(47)(48). These networks are sensitive to disruption of high degree proteins (proteins with numerous interaction partners, also named hub genes) (49,50) since protein degree correlates with its gene essentiality for phenotype survival.…”
Section: Discussionmentioning
confidence: 99%